Land use strategies in Pucallpa, Perú - Fujisaka, Sam (International Center for Tropical Agriculture, 1997)
In a selected study are in Pucallpa, Peru, 151 farmer-settlers were interviewed to understand current land use dynamics. Respondents were stratified according to broad differences determined by preliminary informal surveys. Settlers included: farmers practicing slash-and-burn agriculture in upper forested areas, slash-and-burn farmers living along rivers, small-scale cattle ranchers with lands located largely along the road connecting Pucallpa to Lima, and a subset of forest slash-and-burn farmers who had established oil palm as a cash crop. This working paper describes land use patterns and differences among these groups. Some of the problems and opportunities faced by each group are considered.